2022
DOI: 10.1111/dme.14927
|View full text |Cite
|
Sign up to set email alerts
|

Developing services to support the delivery of care to people with early‐onset type 2 diabetes

Abstract: Early-onset type 2 diabetes occurring in childhood or early adulthood carries a significant excess burden of microvascular diabetes complications, cardiovascular disease and premature death, compared to later onset type 2 diabetes along with adverse pregnancy outcomes in women of child-bearing age. National audit data in England reveal that 122,780 individuals under the age of 40 years are currently living with type 2 diabetes, with an over-representation of people from minority ethnicities and those in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…These approaches must include a focus on strategies that engage people of working age, women of child‐bearing age and indeed those that are tailored to people from deprived communities of any ethnic group and those from minority ethnic groups. 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches must include a focus on strategies that engage people of working age, women of child‐bearing age and indeed those that are tailored to people from deprived communities of any ethnic group and those from minority ethnic groups. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the underlying drivers for poor outcomes, these results suggest there will be a need for novel approaches to care provision in those living with type 2 diabetes under the age of 40 years. These approaches must include a focus on strategies that engage people of working age, women of child‐bearing age and indeed those that are tailored to people from deprived communities of any ethnic group and those from minority ethnic groups 30 …”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis of behavioural interventions aimed at improving self‐management in young adults with type 1 and 2 diabetes found that glycaemic levels did not significantly improve, 8 contrasting with the positive findings from systematic reviews conducted in type 2 diabetes in general 9 . A recent review has emphasized the need for better engagement and novel approaches for self‐management in YOD 10 …”
Section: Introductionmentioning
confidence: 99%
“…9 A recent review has emphasized the need for better engagement and novel approaches for selfmanagement in YOD. 10 The American Association of Diabetes Educators (AADE) described the main factors impacting selfmanagement and categorised them as knowledge, skills and barriers. 11 Diabetes knowledge is fundamental to self-management.…”
Section: Introductionmentioning
confidence: 99%
“…Health inequalities are prevalent, complex and represent a significant barrier to public health. Deprivation is a significant factor for access to type 1 diabetes technologies 1 and for the effectiveness of education interventions 2 while the importance of addressing health inequalities to optimise outcomes for those at greatest risk is critical when developing services to support the delivery of care to people with early‐onset type 2 diabetes 3 . Importantly, while the use of type 1 diabetes technologies is related to deprivation, outcomes are not, suggesting that institutional, infrastructure and individual factors at the healthcare provider level should be addressed to remove inequalities.…”
mentioning
confidence: 99%